Effect of natural antioxidants on bond strength recovery of resin‐modified glass ionomers to the NaOCl‐affected pulp chamber dentin. Issue 1 (15th December 2022) - Shafiei, Fereshteh; Dehghani, Zahra; Tavangar, Maryam S.
Abstract: Objective: This study evaluated the effect of two natural antioxidants on the compromised bond strength of a resin‐modified glass ionomer (RMGI) to the sodium hypochlorite (NaOCl)‐affected pulp chamber dentin. Methods: Forty‐two sound third molars were split into halves. The exposed pulp chamber dentin was ground to provide the flat dentin surfaces and divided into seven groups ( n  = 12), according to the solutions used for immersion: (1) Control, distilled water; (2) NaOCl, 5.25% NaOCl for 20 min; (3) NaOCl/Ethylenediaminetetraacetic acid (EDTA); 5.25% NaOCl for 20 min + 17% EDTA for 1 min; (4) NaOCl/TA, 5.25% NaOCl + 10% tanic acid (TA) for 5 min; (5) NaOCl/EDTA/TA, 5.25% NaOCl + 17% EDTA + 10% TA for 5 min; (6) NaOCl/PA, 5.25% NaOCl+ 10% proanthocyanidin for 5 min; and (7) NaOCl/EDTA/PA, 5.25% NaOCl+ 17% EDTA + 10% PA for 5 min. The RMGI was bonded on the treated dentin using a Tygon tube. After 24 h of storage, microshear bond strength (µSBS) was tested. Data in MPa were submitted to one‐way analysis of variance and Tamhane test. Results: NaOCl significantly decreased the µSBS; NaOCl/EDTA and NaOCl/TA significantly increased the µSBS, higher than the control group ( p  < .05); and in the NaOCl/EDTA/TA group, the increased bond strength was at the level of the control group ( p  > .05). NaOCl/PA and NaOCl/EDTA/PA and NaOCl groups had comparable µSBS. Conclusion: TA could be suggested to provide effective bonding of RMGI and immediate sealing of the pulp chamber dentin after NaOCl irrigation.